Role of Perceived Customer Service, Quality, and Price Fairness on Attitude Formation: An Empirical Evidence from Nepal’s Online Business Context - Rai, Arjun (Journal of Management, 2022)
Extensive development of information communication technology has widened the entrepreneurial opportunities and improved the multidimensional connectivity across the globe. Nepal does not stand aloof from this reality. At the same time, an abrupt outbreak of covid-19 crippled the global economy compelling many enterprises to face the unthought situation and act on issues unanticipated. Nepal’s small and medium enterprises were forced to change their operation and marketing activities to reach customers. As a result, many small-sized enterprises started promoting thei products online, especially on social networking sites, accepted orders, payments online, and cash on delivery. Amid such a situation, this study aimed to identify how individuals perceive the customer services provided by online stores in Nepal. Further, this study also examined the role of perceived customer service, quality, and price fairness in shaping the attitude towards online shopping. This research applied the Ordinary Least Square to find out the effect of perceived customer service, quality, and price fairness on the attitude toward online shopping. Data was collected from 425 respondents through an online questionnaire. The collected data were processed in the Statistical Package for Social Science (25). The result of the study suggested a significant positive impact of perceived customer service, quality perception, and price fairness perception on attitude. The contribution of this study is the understanding of the relationship between the variables used in this study and the impact of the independent variable on the dependent variable in the Nepalese context. The results of this study may be helpful to the marketers in improving perceived customer service, quality perception, and price fairness and eventually increasing their sales.